Molinism the contemporary debate - Perszyk, Kenneth J. (Oxford : Oxford University Press, 2011)
Molinism promises the strongest account of God's providence consistent with our freedom. But is it a coherent view, and does it provide a satisfying account of divine providence? The essays in this volume examine the status, defensibility, and application of this recently revived doctrine.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Molinism